Deficiency of transcription factor Nkx6.1 does not prevent insulin secretion in INS-1E cells - Pavluch, Vojtěch; Engstová, Hana; Špačková, Jitka; Ježek, Petr (Scientific reports, 2023)
Pancreatic-β-cell-specifying transcription factor Nkx6.1, indispensable for embryonic development of the pancreatic epithelium and commitment to β-cell lineage, directly controls the expression of a glucose transporter (Glut2), pyruvate carboxylase (Pcx), and genes for insulin processing (endoplasmic reticulum oxidoreductase-1β, Ero1lb; zinc transporter-8, Slc30a8). The Nkx6.1 decline in aging diabetic Goto-Kakizaki rats contributes to β-cell trans-differentiation into δ-cells. Elucidating further Nkx6.1 roles, we studied Nkx6.1 ablation in rat INS-1E cells, prepared by CRISPR/Cas9 gene editing from single colonies. INS-1ENkx6.1-/- cells exhibited unchanged glucose-stimulated insulin secretion (GSIS), moderately decreased phosphorylating/non-phosphorylating respiration ratios at high glucose; unchanged but delayed ATP-elevation responses to glucose; delayed uptake of fluorescent glucose analog, but slightly improved cytosolic Ca2+-oscillations, induced by glucose; despite approximately halved Glut2, Pcx, Ero1lb, and Slc30a8 expression, and reduced nuclear receptors Nr4a1 and Nr4a3. Thus, ATP synthesis was time-compensated, despite the delayed GLUT2-mediated glucose uptake and crippled pyruvate-malate redox shuttle (owing to the PCX-deficiency) in INS-1ENkx6.1-/- cells. Nkx6.1 thus controls the expression of genes that are not essential for acute insulin secretion, the function of which can be compensated for. Considerations that Nkx6.1 deficiency is an ultimate determinant of β-cell pathology beyond cell trans-(de-)differentiation or β-cell identity are not supported by our results.
Keywords: Insulin; krysa rodu Rattus; Adenosine Triphosphate; adenosintrifosfát; Glucose; Insulin-Secreting Cells; Animals; sekrece inzulinu; Homeodomain Proteins; inzulin; glukosa; Transcription Factors; transkripční faktory; homeodoménové proteiny; Insulin Secretion; zvířata; beta-buňky; Rats